Thermodynamics : - Cengel, Yunus A. (McGraw-Hill Higher Education, 2006)
The worldwide bestseller Thermodynamics: An Engineering Approach brings further refinement to an approach that emphasizes a physical understanding of the fundamental concepts of thermodynamics. The authors offer an engineering textbook that "talks directly to tomorrow's engineers in a simple yet precise manner, that encourages creative thinking, and is read by the students with interest and enthusiasm." The new edition features an early introduction of the first law of thermodynamics, separate coverage of closed systems energy analysis, combined coverage of control volume mass and energy analysis, and revised coverage of compressible flow. Over 300 comprehensive problems have been added to this physically intuitive text, many of which come from industrial applications.